Trends in exposure to respirable crystalline silica (1986-2014) in Australian mining - Peters, S.; Vermeulen, R.; Fritschi, Lin; Musk, A.; Reid, Alison; de Klerk, N. (2017)
© 2017 Wiley Periodicals, Inc. Background: Respirable crystalline silica (RCS) has been associated with severe health risks. Exposures in Western Australia (WA) have been typically high in hard-rock mining and have reduced substantially since the mid-1900s. We described trends in RCS exposure in WA miners over the past 30 years. Methods: A total of 79 445 reported personal RCS exposure measurements, covering the years 1986-2014, were examined. Mixed-effects models were applied to estimate RCS exposure levels, including spline terms to estimate a time trend. Results: An overall downward trend of about -8% per year was observed for RCS exposures in WA mining. Highest RCS exposure levels were modeled for base metal mining and exploration settings. Drilling occupations were among the highest exposed jobs. Conclusion: RCS exposure levels have fallen considerably in the last three decades. However, there are still mining occupations that may need further attention to avoid adverse health effects in these workers.